Advancing Dinner Timing Is an Effective Strategy in Improving Glucose Tolerance in Free-Living Adults: A Randomized Cross-Over Trial. (29th May 2020) - Dashti, Hassan; Lopez, Jesus; Vetter, Céline; Pérez-Ayala, Millán; Baraza, Juan Carlos; Florez, Jose; Saxena, Richa; Scheer, Frank; Garaulet, Marta
Abstract: Objectives: Eating at times that conflict with our physiology and coincide with the biological evening has been associated with increased disease risk. In free-living adults from the ONTIME-MT study ( # NCT03036592) study, we tested the hypothesis that advancing the timing of dinner relative to bedtime, simulated by advancing an evening oral glucose tolerance test (OGTT), will result in improved glucose control. Methods: In a randomized, cross-over study design, following an 8h fast, each participant underwent two evening 2-hour 75-gram oral OGTT: early and late (4h vs. 1h prior to habitual bedtime), simulating early and late dinner timing. Habitual bedtime was determined using one-week of electronic sleep logs via smartphone application. The OGTT order was randomized and separated by 1-week washout period. Light intensity was kept bright (≥450 lux) and dim (0–25 lux) in the early and late conditions, respectively. Melatonin was assessed at the start and end of each OGTT by radioimmunoassay. Postprandial glucose and insulin were determined using incremental area under the curve (AUC). Insulin sensitivity and beta-cell function were evaluated using standard metrices: insulin sensitivity index (ISI), corrected insulin response (CIR), and disposition index (DI). Values were compared using paired t-tests and differences were considered significant at P < 0.05. Results: A total of 750 participants (mean age = 37 ± 14; 70% female; mean BMI = 26.12 ± 5.66) underwent OGTTs in two evening timing conditions. As expected, melatonin levels were higher in the late vs. early condition (4.49 ± 4.15-fold lower in the early vs. late meal condition. In the early condition, there was an 8.68% lower AUC for glucose ( P = .0001) and 4.4% higher insulin AUC ( P = 0.059), relative to the late condition. In addition, the CIR was 16% ( P = .0001) higher and the DI was higher by 20% ( P = .014) in the early compared to the late condition. The ISI was similar in both conditions ( P = 0.66). Conclusions: In this large study, glucose tolerance was better during early vs. late evening OGTT. Better glucose tolerance was primarily attributed to improved insulin secretion and beta-cell function. These results indicate that for the general population, advancing dinner relative to bedtime may be a novel and an effective strategy to improve glucose tolerance. Funding Sources: ONTIME-MT was funded by the NIH R01 grant R01DK105072.